Penilaian Sekolah Binaan YPA-MDR Area Kapuas dan Barito - Setiawan, Indra; Prasetyani, Lin; Ardi, Syahril; Wicaksono, Andreadie; Nugraha, Afitro Adam (Universitas Nusantara PGRI Kediri, 2024)
Nowadays, school development is very important to maintain the quality of the learning process. After developing a program or activity, an evaluation is usually carried out to evaluate its effectiveness and achievements. Assessment is an activity to find valid information. This search also includes searching for information that is useful for assessing the existence of a program and alternative strategies offered to achieve predetermined goals. The assessment of these schools can be called Community Service (PkM) activities. This PkM aims to evaluate the performance of schools supported by the Astra Education Foundation - Michael D'Ruslim (YPA-MDR) to maintain the quality of education. This activity is carried out by visiting schools. The target of this activity is all schools supported by YPA-MDR in the Kapuas and Barito areas of Central Kalimantan. The results of this activity provide benefits to all schools to find out the level of education quality of each school. The results can be concluded that academic and character criteria still dominate at the top, followed by non-academic criteria (arts and culture) and other supporting programs (facilities - infrastructure). The academic pillar is the main point considering that the assessment is an educational institution, where learning criteria are very important to review.